Regional collaboration in the context of Zika virus in Southeast Asia: the development of the zika operational guidelines for the preparedness and response of Southeast Asian countries, 1st edition - Royce Tsukayama; Soawapak Hinjoy; Pensom Jumriangrit; Walaiporn Jiaranairungroj (Taylor & Francis Group, 2020)
The considerable health, social and economic implications of Zika virus along with the World Health Organization's declaration of a Public Health Emergency of International Concern in 2016, led to the gathering of Southeast Asian countries for a committed response to Zika virus in Southeast Asia. For the technical and collaborative efforts to be successful, existing gaps had to be overcome. Guidance for relevant authorities to build preparedness and response capacities, enhancement of networks, and the provision of a forum to share best practices of Zika and mosquito-borne diseases across the region were still needed to address Zika virus as a global health security threat. Operating outside of formal structures, government health officials from Southeast Asian countries assembled to update knowledge, share experiences, and develop a comprehensive framework that could navigate Zika virus prevention and control. This framework would include guidelines that encompass cross-sectoral efforts including 1) Surveillance, Outbreak Investigation, and Containment, 2) Laboratory Detection, 3) Zika in Healthcare Facilities, 4) Prevention and Vector Control, and 5) Coordination and Risk Communication. The result of the unofficial network was a candid dialogue between government officials on best practices and a functional, adaptable set of Zika virus operational guidelines specific to Southeast Asia.